River water quality treatment using phytoremediation of vetiver grass - Hasan, S. N. M. S.; Mohd Kusin, Faradiella; Yusuff, F. M.; Ibrahim, Z. Z. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Phytoremediation technique is one the cost-effective technique in removing contaminants and toxic chemicals from polluted river. The key objective of this project is to study the effectiveness of vetiver grass in removing pollutants and improving water quality at polluted river using phytoremediation system. Guideline for field installation of passive vetiver treatment system for running water also has been develop in this project. In the study, vetiver grass (Vetiveria zizanioides) was used in the phytoremediation treatment due to its ability in absorbing large amount of pollutants and nutrients content for purification of polluted sites. The vetiver grass has been evaluated for their capability of removing pollutants in laboratory experiments (controlled environment) and in the field (uncontrolled environment). Findings indicated that iron (Fe) showed the highest removal efficiency (98%) of heavy metal, while Water Quality Index (WQI) showed 10% improvement after installation of vetiver system. Overall, it has been shown that vetiver grass can be effectively used in phytoremediation of pollutants such as for heavy metals, organic constituents and nutrients in static and flowing water.